2012
DOI: 10.4322/rbcv.2014.075
|View full text |Cite
|
Sign up to set email alerts
|

Causas de condenações post-mortem de perus abatidos em estabelecimento com Serviço de Inspeção Federal (SIF) no estado de Minas Gerais, Brasil

Abstract: ResumoEste estudo objetivou identificar as principais causas de condenações de perus abatidos sob Serviço de Inspeção Federal, além de verificar as estações do ano em que as condenações são mais frequentes. Dentre o número total de condenações post-mortem, 99,06% foi devido a condenações parciais e 0,94% devido a condenações totais. As causas de condenação parcial mais frequentes foram devido à aerossaculite (41,24%), seguida de contaminação biliar (23,73%). As causas de condenação total mais frequentes foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
1
1
Order By: Relevance
“…In a study in two slaughterhouses in Midwestern Brazil, Santana et al (2008) found a small percentage of condemnations by cellulitis and attributed it to broiler management. Condemnations by airsacculitis in the current study were relatively low when compared with those found by Moura et al (2012). The inflammation of one or more of the air sacs was also the most significant cause of partial turkey carcass condemnation described by Macahyba et al (2005) in a study in Southern Brazil.…”
Section: Discussioncontrasting
confidence: 61%
“…In a study in two slaughterhouses in Midwestern Brazil, Santana et al (2008) found a small percentage of condemnations by cellulitis and attributed it to broiler management. Condemnations by airsacculitis in the current study were relatively low when compared with those found by Moura et al (2012). The inflammation of one or more of the air sacs was also the most significant cause of partial turkey carcass condemnation described by Macahyba et al (2005) in a study in Southern Brazil.…”
Section: Discussioncontrasting
confidence: 61%
“…Há apenas quatro levantamentos registrados na literatura em relação ao índice de condenação em abatedouros de perus; são estes: Macahyba et al (2005), Schletein (2007), Abujamra (2010) e Moura et al, (2012), sendo, no presente estudo, a condenação por aerossaculite muito mais elevada em três deles; apenas Moura et al (2012), no estado de Minas Gerais, teve índices mais elevados (41,24%, 722.119 carcaças condenadas).…”
Section: Resultsunclassified